Using scenarios in multinational companies across geographic distances – a case from the chemical industry. Issue 5 (14th September 2015) - David Sarpong, Dr. Martin Nils Amstéus, Dr. Joseph Amankwah-Amoah, Dr.; Hartmann, David; Stillings, Christopher
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to describe the context and relevance of strategic foresight in the chemical industry. By using a case study of a multinational chemical company, the authors intend to show how global organizations use scenario planning as part of their strategic planning processes. Concentrating on scenario planning for regional strategies, the authors want to contribute to best practice of scenario methodology and ideally inspire academic research. Design/methodology/approach – Reviewing the literature of scenario planning and strategy elaboration, the authors focus on the Hax strategy process of strategy formation, as been applied in the case study's company. They explain the scenario creation process in detail using a concrete example of India. The outcomes of the scenario creation process are then linked to the Hax strategy process's description, to identify where scenario planning has created concrete value. Finally, the authors describe lessons learnt and list best practices for practitioners. Findings – Based on the analysis, the authors argue that scenario processes add value when embedded in established strategic planning processes. Lessons learned include among others that it is beneficial that the participants creating the scenarios are also those who join the strategy elaboration and that significant effort needs to go into systematically translating scenarios into implications for the organization. Originality/value – This designed case study is based on the experience of 17 process iterations during a period of five years with over 170 participants during which the core scenario process moderator team did not change.